Performance measurement in finance : firms, funds and managers - Knight, John L.; Satchell, Stephen, 1949- (Quantitative finance series., 2002)
The distinction between out-performance of an Investment fund or plan manager vs rewards for taking risks is at the heart of all discussions on Investment fund performance measurement of fund managers. This issue is not always well-understood and the notion of risk adjusting performance is not universally accepted. Performance Measurement in Finance addresses this central issue. The topics covered include evaluation of investment fund management, evaluation of the investment fund itself, and stock selection performance. The book also surveys and critiques existing methodologies of performance m.